Religious Values On Poems of Ziaroh 1 (Nilai Religi Pada Puisi Ziaroh 1) - Kodrat Eko Putro Setiawan (Jurusan Tadris Bahasa Indonesia, 2018)
This research aims to reveal the meaning of Riffaterre semiotic approach through heuristic reading, hermeneutic reading, matrix, model, variant, hypogram, and poetry relevance entitled Ziaroh 1 with Islamic teachings. The method used is a qualitative interpretive method with content analysis. The results of this study are: 1) in the heuristic reading, there are thirteen lines referentially meaning the words in the poem are derived from KBBI; 2) on hermeneutic readings, there are thirteen lines that have the meaning of an activity (pilgrimage) in remembrance of a deceased person, ie mother; 3) bermatriks, a child who misses his late mother; 4) modeled, poetic and all forms of action derived from the